Gestão da maturidade: uma proposta de ferramenta para a avaliação da maturidade em BPM (Business Process Management) nas micro e pequenas empresas - Silva, Ramon Scherrer da (Universidade do Vale do Rio dos Sinos, 2015)
This paper aims to develop a tool to assess the level of maturity of micro and small enterprises (SMEs) in business processes management (BPM). To perform it, we collected 473 publications on the subject, published between 2010 and 2015, available on the Google Scholar database. After analyzing title, abstract and keywords of these publications, we have selected those directly related to the subject of this study, resulting in 54 publications. Then, we analyzed all publications and identified ten relevant maturity models, which were analyzed according to their contribution to answer the main question of this study. We verified that the model with the highest academic and practical contribution, considered the most sophisticated in terms of its holistic approach and academic originality, was the BPM Maturity Model (BPMMM), developed by Rosemann and Bruin (2005). After choosing a model, we developed the tool to assess the maturity of BPM, which is the major contribution of this study, as well as the fact of bringing up the topic in the context of SMEs, showing that BPM can be adopted as business strategy, without necessarily accomplishing major investments.
Keywords: Maturidade; Gestão de processos de negócio; Micro e pequenas empresas; Modelos de avaliação de maturidade; Maturity; Business processes management; Micro and small enterprises; Maturity model assessment